Antenatal care for alcohol consumption during pregnancy: pregnant women's reported receipt of care and associated characteristics - Emma Doherty; John Wiggers; Luke Wolfenden; Amy E. Anderson; Kristy Crooks; Tracey W. Tsang; Elizabeth J. Elliott; Adrian J. Dunlop; John Attia; Julia Dray; Belinda Tully; Nicole Bennett; et al. (BMC, 2019)
Abstract Background Antenatal clinical guidelines recommend that during initial and subsequent antenatal visits all pregnant women: have their alcohol consumption assessed; be advised that it is safest not to consume alcohol during pregnancy and of the potential risks of consumption; and be offered referrals for further support if required. However, the extent to which pregnant women attending public antenatal services receive guideline recommended care at these visits, and the characteristics associated with its receipt, is unknown. The purpose of this study was to examine: 1) pregnant women's reported receipt of guideline recommended care addressing alcohol consumption during pregnancy; 2) characteristics associated with the receipt of care; and 3) pregnant women's acceptability of care. Methods From July 2017 - February 2018 a survey (telephone or online) was undertaken with 1363 pregnant women who had recently visited a public antenatal service in one health district in Australia. Receipt and acceptability of recommended care were assessed via descriptive statistics and associations via logistic regression analyses. Results At the initial antenatal visit, less than two thirds (64.3%) of pregnant women reported that they received an assessment of their alcohol consumption and just over one third (34.9%) received advice and referral appropriate to their self-reported level of alcohol consumption since pregnancy recognition. Less than 10% of women received such care at subsequent antenatal visits. Characteristics that significantly increased the odds of receiving all guideline elements at the initial antenatal visit included: less than university attainment (OR = 1.93; 95% CI:1.12, 3.34), not residing in an advantaged area (OR = 2.11; 95% CI:1.17, 3.79), first pregnancy (OR = 1.91; 95% CI:1.22, 2.99) and regional/rural service location (OR = 2.38; 95% CI:1.26, 4.48); and at subsequent visits: younger age (OR = 0.91; 95% CI:0.84, 0.99) and Aboriginal origin (OR = 3.17; 95% CI:1.22, 8.24). Each of the recommended care elements were highly acceptable to pregnant women (88.3-99.4%). Conclusions Although care for alcohol consumption is both recommended by clinical guidelines and highly acceptable to pregnant women, its receipt in public antenatal services is suboptimal. There is a need and an opportunity for interventions to support antenatal care providers to routinely and consistently provide such care to all pregnant women.